Democracy for breakfast : unveiling mirage democracy in contemporary Africa - Mentan, Tatah, 1948- (Langaa Research and Publishing CIG, 2013)
Democracy is the faith that the process of experience is more important than any special result attained, so that special results achieved are of ultimate value only as they are used to enrich and order the ongoing process. Africans must therefore be allowed to apply their cultural and historical experiences and talents in working out a pattern of ëgovernment of the people, by the people, and for the peopleí according to their own understanding and as their own peculiar circumstances demand. Those who do not want the vertical ëWestern-Style Democracyí must be given a fair chance to demonstrate.